Physiochemical characterization of lateritic bauxite mining soil - N. I., N. Ismai; Haryati, Awang; N. Z., Mohd Yunus; Suriyati, Saleh (IOP Publishing Ltd, 2021)
Physiochemical characteristics play a significant role in evaluating the engineering behaviour of soil material and its suitability for foundation. Investigation upon the physical and chemical characteristics of lateritic bauxite soils were done on samples collected from three exmining bauxite sites (Bukit Goh, Semambu and Indera Mahkota) in Kuantan District, Pahang, Malaysia. The presence of chemical element was evaluated based on the elemental mineral composition content identified through X-Ray Fluorescence (XRF). The results revealed that Semambu lateritic bauxite soil has the highest content of alumina (Al2O3), 25.54%. The alumina content enrichment is one of the effects from the laterization of bauxite process. In addition, the physical testing included are moisture content, specific gravity and Atterberg Limit. Further investigation on the physical properties of the soil has found that Semambu has the highest MC, 33.27%, but at the same time PI is less than 12%. This is as a key indicator that lateritic bauxite is prone to surface erosion and unsuitable for construction purposes in its natural condition. The risk of the surface erosion and settlement of the ground causes it requires stabilizer that can rapid the curing time. Additionally, the high moisture content is likely to have higher chance to experience liquefaction and causes foundation problem to future infrastructures that may be built in the studied area.